Viral Infections Among Patients with Acute Lower Respiratory Tract Infections in the Pediatric Intensive Care Unit - Sik, Guntulu; Demirbuga, Asuman; Annayev, Agageldi; Cabiri, Asli; Deliceo, Elif; Citak, Agop (AVES YAYINCILIK, IBRAHIM KARA, 2020)
Objective: We aimed to determine the frequency of viral pathogen and clinical characteristics of patients hospitalized in the pediatric intensive care unit with the diagnosis of acute lower respiratory tract infection. Material and Methods: Eighty patients with laboratory-confirmed viral infections among children admitted to the pediatric intensive care unit (PICU) between November 2016 and September 2017 with a suspicion of viral infection were included. Diagnosis was made using a respiratory viral panel including adenovirus (AV), metapneumovirus (MV), parainfluenza virus (PIV) 1, PIV 2, PIV 3, PIV 4, influenza virus (IV) A and IVB, rhinovirus (RV), respiratory syncytial virus (RSV) A and RSV B, and multiplex polymerase chain reaction (PCR). Tracheal aspiration specimens were obtained from intubated patients and nasopharyngeal swab specimens were obtained from the remaining patients. Results: A total of 514 children were admitted to our PICU. Of 123 patients with lower respiratory tract infection, specimens from a nasopharyngeal swab or tracheal aspiration were obtained and tested using a viral infection panel and multiplex PCR. Mean age of the patients was 6.1 +/- 3.6 months, 60\% (n= 48) of the children were boys. Ninety-three positive results were obtained from 80 patients. The most common viral pathogens were RSV (A + B) (n= 36, 45\%), RV (n= 26, 32.5\%), PIV 1 (n= 7, 8.7\%), AV (n=6, 7.5\%), human MV (n= 5, 6.296), IVA (n= 4, 5\%), and IVB (n= 4, 5\%). The most common dual infection was RV and RSV B. Viral pathogen detection was the highest in december (n= 15) and february (n= 13). High-flow oxygen therapy was needed in 57.5\% of patients, and 12.5\% had non-invasive mechanical ventilation. Twenty-seven (33.7\%) patients had to be intubated due to insufficient ventilation with noninvasive methods. The most commonly detected viral pathogen among the intubated patients was RSV B. The average intensive care length of stay for all children was 10.1 +/- 3.6 days. Conclusion: Viral infections are common among critically ill children in PICUs. Hospital length of stay, morbidity, and mortality increase with underlying chronic diseases or dual infections. Early diagnosis of viral infections decreases unnecessary antibiotic use.
Keywords: Pediatric intensive care; viral infection; lower respiratory tract infections; multiplex PCR; respiratory viral panel